Solitude as a state of positive aloneness in childhood and adolescence - Galanaki, Evangelia (J. Kowalski, J. P. Cangemi, & A. Rokach (Eds.), Loneliness in life: Education, business, and society, 2015)
If solitude, as a state of being alone, is a basic human need equally important to attachment and belonging, it is necessary to explore its multiple positive contributions to children's and adolescents' development. However, this type of solitude is a relatively neglected research area in these age periods. Research evidence on the existence, significance, and developmental course of positive aloneness experiences is the focus of this chapter beginning with some clarifications on the various concepts of aloneness (i.e., loneliness, aloneness, solitude, attitude toward aloneness, privacy). Next, research is reviewed on assessment of aloneness and solitude; understanding and content of solitude; assessment of aloneness and solitude; amount, context, and affect of time alone; attitude toward aloneness; the links between solitude and adjustment; the associations between solitude and strategies of coping with loneliness; and the associations between solitude and other aloneness concepts. Data on gender differences also are discussed. Finally, suggestions are offered fo rfuture research on this type of solitude in childhood and adolescence.